Off-shell persistence of composite pions and kaons - Qin, Si-Xue; Chen, Chen [UNESP]; Mezrag, Cédric; Roberts, Craig D. (American Physical Society (APS), 2018)
In order for a Sullivan-like process to provide reliable access to a meson target as t becomes spacelike, the pole associated with that meson should remain the dominant feature of the quark-antiquark scattering matrix and the wave function describing the related correlation must evolve slowly and smoothly. Using continuum methods for the strong-interaction bound-state problem, we explore and delineate the circumstances under which these conditions are satisfied: for the pion, this requires -t0.6GeV2, whereas -t0.9GeV2 will suffice for the kaon. These results should prove useful in planning and evaluating the potential of numerous experiments at existing and proposed facilities.